FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI INFORMASI PELAPORAN KEUANGAN PADA SATUAN KERJA PERANGKAT DAERAH KOTA PEKANBARU - irena puspi hastuti; Wahyuningsih Wahyuningsih; Tri Putri Indirayana (Politeknik Keuangan Negara STAN, 2021)
The purpose of this research is to examine the effect of the quality of human resources, the use of information technology, and internal control systems on the value of financial reporting information at the Pekanbaru City SKPD. Determination of the sample using purposive sampling technique. The sample in this study was the head of the finance division, treasurer and finance staff who were in 44 SKPD Pekanbaru City with the number of respondents amounting to 176 people. The method used is a quantitative method with the type of survey research. Based on the results of partial and simultaneous research, the results of this study indicate that the quality of human resources, the use of information technology and internal control systems significantly influence the value of financial reporting information for the Pekanbaru City Regional Apparatus Work Unit. And it can be concluded that there are other individual aspects that can explain the Value of Local Government Financial Reporting.